Information and Communication Technology Scenario of Nepal: Assessing Policy Environment and Challenges - Bhattarai, Manohar Kumar (Nepal Public Policy Review, 2021)
Advances in Information and Communication Technologies (ICTs) offer great opportunities for developing countries to stimulate economic growth. However, Nepal has not been able to harness the full potential of the ICTs and benefit from them to the extent possible because of the general absence of underlying fundamentals including policies and strategies aligned with the technological dynamism of the sector, to address ever evolving needs and fully capitalize on opportunities offered ICTs and digital technologies. To rise to the ICT challenge facing the country requires a thorough review of structural impediments to the transformative potential of ICTs and digital technologies, establishment of the policy environment that promotes innovative harnessing of these technologies by all actors, including the private sector, and a strategic orientation that factors in fast evolving technology landscape, where artificial intelligence, blockchain, analytics and Industry 4.0 are set to play defining roles going forward.